TEKNIK MEDITASI DAN AFIRMASI POSITIF UNTUK PENATALAKSANAAN KEHAMILAN DENGAN KELUHAN NYERI PUNGGUNG BELAKANG PADA IBU N DI DESA SUAK PANDAN KECAMATAN SAMATIGA KABUPATEN ACEH BARAT - Ulfia Dari; Yushida Yushida; Nanda Norisa; Rina Julianti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
During pregnancy, physical and psychological changes occur, causing discomfort for the mother, which can then impact the well-being of the fetus. Therefore, management efforts are needed to minimize the impacts that occur. Meditation and positive affirmations can be an alternative, one of the non-pharmacological therapies claimed to have a positive effect on the physical and psychological health of the mother and are beneficial for the health of the fetus, such as reducing excessive anxiety and pain. The implementation of meditation and positive affirmations in community service aims to provide information and empower mothers during pregnancy to improve health. This activity is carried out in three stages. The first stage is a pre-test, the second stage is the delivery of material and practice of meditation and positive affirmations, and the third stage is a post-test. The results show a difference in the level of knowledge and complaints with a p-value of 0,000 for each variable. There is a difference in the level of anxiety of the target group compared between the pretest and post-test. With a p-value of 0,001. It can be concluded that the application of meditation and positive affirmations is effective in increasing knowledge, reducing complaints, and reducing the level of anxiety of pregnant women.